Electrochemical Studies of a Truncated Laccase Produced in Pichia pastoris - Gelo-Pujic, Mirjana (American Society for Microbiology, 1999)
The cDNA that encodes an isoform of laccase from Trametes versicolor (LCCI), as well as a truncated version (LCCIa), was subcloned and expressed by using the yeast Pichia pastoris as the heterologous host. The amino acid sequence of LCCIa is identical to that of LCCI except that the final 11 amino acids at the C terminus of LCCI are replaced with a single cysteine residue. This modification was introduced for the purpose of improving the kinetics of electron transfer between an electrode and the copper-containing active site of laccase. The two laccases (LCCI and LCCIa) are compared in terms of their relative activity with two substrates that have different redox potentials. Results from electrochemical studies on solutions containing LCCI and LCCIa indicate that the redox potential of the active site of LCCIa is shifted to more negative values (411 mV versus normal hydrogen electrode voltage) than that found in other fungal laccases. In addition, replacing the 11 codons at the C terminus of the laccase gene with a single cysteine codon (i.e., LCCI→LCCIa) influences the rate of heterogeneous electron transfer between an electrode and the copper-containing active site (k(het) for LCCIa = 1.3 × 10(−4) cm s(−1)). These results demonstrate for the first time that the rate of electron transfer between an oxidoreductase and an electrode can be enhanced by changes to the primary structure of a protein via site-directed mutagenesis.